2016
DOI: 10.1111/pedi.12430
|View full text |Cite
|
Sign up to set email alerts
|

Curative potential of allogeneic hematopoietic stem cell transplant in type 1 diabetes

Abstract: The mainstay of treatment for type 1 diabetes (T1D) is exogenous insulin. Here, we report a case in which exogenous insulin requirements were eliminated after allogeneic hematopoietic stem cell transplant for aplastic anemia in a pediatric patient recently diagnosed with T1D, and explore the validity of this approach compared to current treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…The period from onset of T1D to HSCT can affect the therapeutic efficacy for T1D with IPEX. In our late‐onset IPEX patient with R347H mutation, we speculated that HSCT rescued the pancreatic β‐cells because the insulin‐dependent diabetes occurred immediately before transplantation; this is well in agreement with the previous reports . Although the patient had acute onset of insulin‐dependent DM, insulin requirement was reduced to half following engraftment, and thereafter, the endogenous insulin secretion was significantly improved, ultimately resulting in withdrawal of insulin.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The period from onset of T1D to HSCT can affect the therapeutic efficacy for T1D with IPEX. In our late‐onset IPEX patient with R347H mutation, we speculated that HSCT rescued the pancreatic β‐cells because the insulin‐dependent diabetes occurred immediately before transplantation; this is well in agreement with the previous reports . Although the patient had acute onset of insulin‐dependent DM, insulin requirement was reduced to half following engraftment, and thereafter, the endogenous insulin secretion was significantly improved, ultimately resulting in withdrawal of insulin.…”
Section: Discussionsupporting
confidence: 90%
“…Recently, it was reported that immune‐based approach of “immunologic reset” with autologous HSCT can preserve β‐cell function and promote long‐term beneficial metabolic effects . In addition, a case of an adolescent with early phase T1D, in which exogenous insulin requirements were eliminated after HSCT for aplastic anemia, was reported . Thus, it was speculated that HSCT for IPEX patients can suppress autoimmunity in multiple organs including pancreas, and reverse the progression of immune‐mediated destruction of pancreatic β‐cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that the increased number of Tregs plays a role in the prevention of T1D. Although it has been reported that other stem cell technology, such as ESC- or induced pluripotent stem cell (iPSC)-derived pancreatic progenitors and allogeneic hematopoietic stem cell transplant have the potential for curing T1D [51, 52], the mechanisms by which our ESC-TECs ameliorate T1D appear to differ from these approaches.…”
Section: Discussionmentioning
confidence: 75%
“… 45 Nevertheless, there are reports of the curative potential of allogeneic HSCT in T1DM, in cases of allogeneic HSCT performed due to other indications, with cure of diabetes as an incidental outcome. 46 , 47 …”
Section: Discussionmentioning
confidence: 99%